Case Report: Ribociclib-induced phototoxicity presented as dyschromia with subsequent bullae formation - Jhan, Jyun-Yan; Wang, Wei-En; Chu, Sung-Chao; Cheng, Chiu-Hsuan; Chang, Chung-Hsing (Frontiers in Oncology, 2023)
Ribociclib, a cyclin-dependent kinase 4/6 inhibitor, is a novel targeted therapy for advanced-stage breast cancer. Although ribociclib-induced cutaneous side effects have been previously noted, they have not been well documented. Herein, we present a case of ribociclib-induced phototoxicity, which manifested as dyschromia over sun-exposed forearms and neck initially and as bullae formation subsequently. A 71-year-old woman with metastatic breast cancer developed dyschromia after daily treatment with ribociclib (600 mg) for 7 months. Skin biopsy of the pigmented lesion revealed interface dermatitis with melanin incontinence and dyskeratotic cells and ballooning keratinocytes with loss of melanocytes in the basal layer. Further, clefting at the basal layer of epidermis was noted in a more hyperpigmented field. Fontana–Masson staining revealed melanophages in the dermis. Human Melanoma Black-45 staining revealed decreased melanocyte numbers in the epidermis above the cleft. Immunohistochemical analyses revealed activated CD1a+ epidermal Langerhans cells and infiltrating CD4+ and CD8+ T cells in the epidermis and dermis, thereby indicating type IV hypersensitivity that was associated with damage to keratinocytes and melanocytes. To prevent progression of bullous dermatitis, we advised the patient to discontinue ribociclib and prescribed oral and topical prednisolone. Due to the risk of phototoxicity, we educated the patient on sun-protection strategies. The patient’s skin lesions subsided during the 2 months of treatment. Phototoxicity with dyschromia is a rare but significant ribociclib-induced cutaneous side effect. Early diagnosis, rapid ribociclib withdrawal, protection from sunlight, and prompt treatment are critical for preventing subsequent severe bullous dermatosis.